Active SB-P Versus Conventional Approach to the Protection of High-Risk Side Branches: The CIT-RESOLVE Trial - Dou, Kefei; Zhang, Dong; Pan, Hongwei; Guo, Ning; Li, Lang; Li, Yue; Zhang, Qi; Liu, Bin; Shen, Zhujun; Zhang, Bin; Liu, Jian; Han, Wei; et al. (JACC. Cardiovascular interventions, 2020)
The aim of this study was to determine whether an active side branch protection (SB-P) strategy is superior to the conventional strategy in reducing side branch (SB) occlusion in high-risk bifurcation treatment. Accurate prediction of SB occlusion after main vessel stenting followed by the use of specific strategies to prevent occlusion would be beneficial during bifurcation intervention. Eligible patients who had a bifurcation lesions with high risk for occlusion as determined using the validated V-RESOLVE (Visual Estimation for Risk Prediction of Side Branch Occlusion in Coronary Bifurcation Intervention) score were randomized to an active SB-P strategy group (elective 2-stent strategy for large SBs and jailed balloon technique for small SBs) or a conventional strategy group (provisional stenting for large SBs and jailed wire technique for small SBs) in a 1:1 ratio stratified by SB vessel size. The primary endpoint of SB occlusion was defined as an angiography core laboratory-assessed decrease in TIMI (Thrombolysis In Myocardial Infarction) flow grade or absence of flow in the SB immediately after full apposition of the main vessel stent to the vessel wall. A total of 335 subjects at 16 sites were randomized to the SB-P group (n = 168) and conventional group (n = 167). Patients in the SB-P versus conventional strategy group had a significantly lower rate of SB occlusion (7.7% [13 of 168] vs. 18.0% [30 of 167]; risk difference: -9.1%; 95% confidence interval: -13.1% to -1.8%; p = 0.006), driven mainly by the difference in the small SB subgroup (jailed balloon technique vs. jailed wire technique: 8.1% vs. 18.5%; p = 0.01). An active SB-P strategy is superior to a conventional strategy in reducing SB occlusion when treating high-risk bifurcation lesions. (Conventional Versus Intentional Strategy in Patients With High Risk Prediction of Side Branch Occlusion in Coronary Bifurcation Intervention [CIT-RESOLVE]; NCT02644434).